Therapy Use for Children With Developmental Conditions: Analysis of Colorado Medicaid Data. Issue 3 (July 2017) - McManus, Beth M.; Rapport, Mary Jane; Richardson, Zachary; Lindrooth, Richard
Abstract : Study Purpose: To examine therapy use and spending for Medicaid-enrolled infants and toddlers with developmental conditions. Methods: Sample infants and toddlers had a diagnosis (eg, cerebral palsy) or developmental delay (DD). Colorado Children's Medicaid administrative outpatient therapy claims (2006-2008) were used to estimate differences, by condition type and number of comorbid chronic conditions (CCCs), of any physical therapy (PT)/occupational therapy (OT) and Medicaid PT/OT spending. Results: The sample included 20 959 children. Children with at least 2 CCCs had higher odds of PT/OT than children with no CCC. Children with DD had 12-fold higher odds of having any PT/OT compared with children with diagnosis. Children with a DD and 2 CCCs had the highest PT/OT spending. Conclusions: Medicaid PT/OT use and spending are higher for children with more CCCs and those with DD because children with DD receive more specialized PT/OT. Abstract : Supplemental Digital Content is Available in the Text.To examine therapy use and spending for Colorado Medicaid-enrolled infants and toddlers with developmental conditions.